„Miłość jest w zasadzie chorobą”. Intymność w listach miłosnych Aliny Szapocznikow do Ryszarda Stanisławskiego - Monika Ładoń (Napis, 2022)
The topic of the article is the interpretation of selected letters from the correspondence of Alina Szapocznikow and Ryszard Stanisławski. The suggested reading aims at taking a closer look at codes of intimacy, activated in the specific life circumstances, in which the sculptor found herself, that is remaining in isolation due to illness. Alina Szapocznikow, struggling with ovarian tuberculosis, writes to her lover, activating the cultural meaning of a place of isolation (hospital and preventorium) as a space of loneliness, which shapes the intimate narrative of the letters. The author of the article examines how the diction of the artist modifies the aforementioned tropes, and the intimacy of an ailing body and a longing for her loved one are regulated by courage and style of the artist. The selected group of letters is treated as an example of love epistolography, and a methodological basis for interpretation is provided by A Lover’s Discourse: Fragments by Roland Barthes and Tales of Love by Julia Kristeva.